Destination Logo Design for Lake Aur Branding at Musi Rawas Regency, South Sumatra Province - Nurul Aini; Irene Hanna H. Sihombing; Widi Hardini (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Lake Aur is a popular tourist destination in Musi Rawas Regency, with an increasing number of visitors every year, mainly from the Musi Rawas area. Despite its popularity among locals, Lake Aur lacks visibility outside the region and needs better branding. The focus is on designing a logo to visually brand Lake Aur, using methods like consultation, observation, interviews, and logo development. The designed logo incorporates colors, slogans, elements, and ideas, and has been successfully applied to merchandise like mugs, key chains, and t-shirts. The aim is to introduce Lake Aur to a wider audience.